The objects of rigidly designating general terms - Robertson, Helen S. (My University, 2009)
Abstract: In Naming and Necessity Kripke introduces rigidity as a feature of certain singular terms and claims that certain general terms are rigid in a way analogous to these singular terms. However, given important dissimilarities between singular and general terms, the question of how Kripke’s notion of rigidity is to be extended from singular to general terms is a significant one. In this paper, I argue for two distinct responses to this question – one an interpretation of rigidity as a feature of general terms, the other an interpretation of rigidity as a feature of predicates. I begin by examining two sophisticated opposing interpretations of general term rigidity – those of Nathan Salmon and Scott Soames. I argue that by distinguishing between a narrower and a broader notion of rigidity within Naming and Necessity, we can find interpretations of both general term and predicate rigidity that overcome the problems faced by Salmon and Soames’s interpretations. I conclude that, in the case of both general term and predicate rigidity, the object rigidly referred to by the term is the relevant universal. This interpretation has a number of adherents in the case of general term rigidity, but is novel in the case of predicate rigidity